Evaluation of the Drainage Channel Capacity of Air Ukah in Ngabang - Barage, Lourdes Meirista; Gunarto, Danang; Soeryamassoeka, S. B. (Fakultas Teknik Universitas Tanjungpura, 2024)
Flooding in Ngabang, Landak Regency, Kalimantan Barat often results from high rainfall, urban expansion, and limited drainage. This study analyzes the Air Ukah drainage system, including primary, secondary, and tertiary channels, to assess current capacities against projected rainfall intensities. Hydraulic and hydrological analyses were performed using primary field data and validated rainfall records from 1999-2020. Findings reveal that the existing drainage, with the primary channel